BANKRUPTCY ANALYSIS USING ALTMAN Z SCORE MODEL IN MANUFACTURING COMPANY AT INDONESIA STOCK EXCHANGE IN 2013-2014 - Suci Kurniawati (Master of Accounting Universitas Trunojoyo Madura, 2017)
Analysis of financial distress is very important, because it enables to assess an indication of the company's financial distress, how the indication of financial distress using Altman z-score in industry manufacturing sector in 2013-2014, and whether the Altman z-score model can be used as a tool in predicting the tendency of financial distress. The purpose of this study is to analyze the financial distress of 125 manufacturing companies with different sectors and subsectors using Altman Z-Score model in 2013 and 2014. The source of data used was secondary data, such as financial statements of manufacturing companies’ publication issued by BEI and obtained from the internet by downloading through the website: www.idx.com. This study employed descriptive quantitative method. The findings of the Z-Score index on manufacturing companies in 2013 were occupied by PT. Intan Wijaya International Tbk. in chemical subsector, and in 2014 Herbal and Pharmaceutical Industry of PT Sido Muncul Tbk. was the first highest rank and healthy condition. Whereas the lowest rank was PT. Asia Pacific Fiber Tbk. in textile and garment sub-sector in 2013 and 2014, having financial distress condition. The findings of this study are not consistent or even in accordance with the reality which shows that the Altman method cannot be used as a tool to indicate a tendency towards company’s financial distress.